MULTICULTURAL INFLUENCES ON LATVIAN ADVERTISING - Ločmele, Gunta (Vertimo studijos, 2017)
This paper examines how multicultural influences have contributed to the formation of Latvian advertising today. It deals with the following features of the Latvian advertising: compression of information, personalization, inclusion, elements of graphic design in written texts and expressive language means. Off-grade advertising texts that often are hidden translations from English do not foster the interest of consumers. However, a positive multicultural impact benefits the development of the Latvian advertising language.